2017
DOI: 10.4102/ojvr.v84i1.1257
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phylogenetic analysis of contagious ecthyma virus from camels (<i>Camelus dromedarius</i>) in Iran

Abstract: Contagious ecthyma is a highly contagious disease affecting domestic and wild ruminants such as sheep, goats and camels. The identification and characterisation of a parapoxvirus (PPV) infecting camels is described here. The virus was detected in dromedary camels (Camelus dromedarius) from Kerman and Shiraz in Iran. PPV-specific amplification by polymerase chain reaction (PCR) further confirmed that the disease was associated with PPV infection. Phylogenetic analysis of ORF011 (B2L) gene sequences showed 99.79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…CPPV was detected by PCR using specific primers which targets the RPO30 gene of the virus. The CPPV has been reported to be more closely related to the Pseudocowpox virus (PCPV), albeit CPPV has also been shown to be related to the Orf virus of sheep and goats (Oryan et al, 2017). Interestingly, in this study, CPPV was detected from the lungs and intestine of camel samples analyzed, whereas, previous studies have reported detection of CPPV in scab samples only (Khalafalla et al, 2015b).…”
Section: Case History and Sample Collectioncontrasting
confidence: 64%
See 1 more Smart Citation
“…CPPV was detected by PCR using specific primers which targets the RPO30 gene of the virus. The CPPV has been reported to be more closely related to the Pseudocowpox virus (PCPV), albeit CPPV has also been shown to be related to the Orf virus of sheep and goats (Oryan et al, 2017). Interestingly, in this study, CPPV was detected from the lungs and intestine of camel samples analyzed, whereas, previous studies have reported detection of CPPV in scab samples only (Khalafalla et al, 2015b).…”
Section: Case History and Sample Collectioncontrasting
confidence: 64%
“…Camel contagious ecthyma (CCE), also called Auzdik disease or Orf is a contagious viral skin disease of camelids that occur in countries with camel husbandry system (Buchnev et al, 1987;Khalafalla et al, 2015a). CCE was first described in Kazakhstan in 1968 and subsequently in the Middle East, some parts of Asia and Africa (Buchnev et al, 1987;Oryan et al, 2017). CCE is caused by a DNA virus of the genus Parapoxvirus (PPV), subfamily Chordopoxvirinae of the family Poxviridae (Khalafalla et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Iran, the digestive form of CE was recorded in 2013 in a 3-week old male yeanling, followed by an outbreak in the entire herd (Mashayekhi et al, 2013). The outbreak was confirmed based on PCR targeting ORF011 (Oryan et al, 2017).…”
Section: Contagious Ecthyma In Asiamentioning
confidence: 99%
“…No studies have been published on camelpox in Kenya since 1997 [40]. Contagious ecthyma, caused by a parapox virus [103,104], was reported in camels in two medium quality studies. One reported on an outbreak of clinical disease in Laikipia in 1984 [47], while the other presented results of a cross-sectional survey in Turkana (Table 4) [46].…”
Section: Virusesmentioning
confidence: 99%